Management of patients with a neurovascular conflict involving the optic nerve and a non-diseased intracranial artery: Three cases - H. Schenck; M. Müther; E. Maragno; M. Holling; M. Cornelissen; R. Haeren (Brain and Spine)
Introduction: Determining whether a neurovascular conflict (NVC) involving the anterior visual pathway (AVP) and a non-diseased intracranial artery is amenable for microvascular decompression is challenging. Moreover, it is unclear whether microvascular decompression of the optic nerve is an effective therapy. Research question: What are the outcomes of different treatment strategies for NVCs involving the AVP and a non-diseased intracranial artery? Material and methods: Data on patients with symptomatic NVCs involving the AVP and a non-diseased intracranial artery was collected and included treatment and outcome parameters. The case series was drafted in accordance with the CARE guidelines. Results: Three patients aged 53,53 and 55 visited our out-patient clinic with a suspected symptomatic NVC between the optic nerve and a non-diseased intracranial artery. A conservative treatment was opted for in the first patient aimed at treating her glaucoma, with temporary improvement of symptoms. Microvascular decompression of the optic nerve was performed in two patients. One operated patient developed post-operative complications resulting in posterior circulation perfusion decline, while the other experienced a worse tunnel vision with a decrease in visual acuity. Discussion and conclusion: The diagnosis of a symptomatic NVC between the AVP and a non-diseased intracranial artery should be considered with caution, i.e. after exclusion of all other causes. Microvascular decompression can be performed but does not necessarily improve symptoms. A better understanding of the pathophysiological mechanisms underlying these NVCs is warranted to determine the benefit of microvascular decompression of the optic nerve.